2022
DOI: 10.3390/plants11212959
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Genetic Effects, Heterosis, and Inbreeding Depression for Phytochemical Traits in Coriander

Abstract: Increasing seed yield, fatty acids, and essential oil content are the main objectives in breeding coriander. However, in order to achieve this, there is a need to understand the nature of gene action and quantify the heterosis and inbreeding depression. Towards this, six genetically diverse parents, their 15 F1 one-way hybrids, and 15 F2 populations were evaluated under different water treatments. The genetic effects of general (GCA) and specific combining ability (SCA) and their interactions with water treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
(84 reference statements)
0
0
0
Order By: Relevance
“…In particular, similar to what emerged in cereals, such as maize (Yang et al, 2017;Liu et al, 2020a;Birdseye et al, 2021), rice (Dan et al, 2014;Shen et al, 2015;Zhu et al, 2016) and wheat (Song et al, 2009), multiple morphological features associated with vegetative tissue also showed different levels of heterosis in vegetable F1 hybrids. These insights, which have been observed depending on the crop and developmental stage, from post-germination to final yield, were derived from Brassicaceae crops, such as Chinese cabbage (Kawamura et al, 2016;Fujimoto et al, 2018;Shiraki et al, 2023), cabbage (Jeong et al, 2017), cauliflower (Verma and Kalia, 2017), rapeseed or canola (Brassica napus L.) (Basunanda et al, 2010;Wolko et al, 2019;Wang et al, 2021;Hu et al, 2022); Solanaceae crops, such as tomato (Chandel et al, 2021;Rajendran et al, 2022), potato (Buso et al, 2003), and eggplant (Kaushik, 2019;Kumar et al, 2020); Apiaceae crops, such as carrot, coriander and caraway (Jagosz, 2011;von Maydell et al, 2021;Hanifei et al, 2022); and Leguminosae crops, such as common bean (Goncalves-Vidigal et al, 2008) and pea (Sharma et al, 2023).…”
Section: Heterosis and The Starting Point Of Knowledgementioning
confidence: 99%
“…In particular, similar to what emerged in cereals, such as maize (Yang et al, 2017;Liu et al, 2020a;Birdseye et al, 2021), rice (Dan et al, 2014;Shen et al, 2015;Zhu et al, 2016) and wheat (Song et al, 2009), multiple morphological features associated with vegetative tissue also showed different levels of heterosis in vegetable F1 hybrids. These insights, which have been observed depending on the crop and developmental stage, from post-germination to final yield, were derived from Brassicaceae crops, such as Chinese cabbage (Kawamura et al, 2016;Fujimoto et al, 2018;Shiraki et al, 2023), cabbage (Jeong et al, 2017), cauliflower (Verma and Kalia, 2017), rapeseed or canola (Brassica napus L.) (Basunanda et al, 2010;Wolko et al, 2019;Wang et al, 2021;Hu et al, 2022); Solanaceae crops, such as tomato (Chandel et al, 2021;Rajendran et al, 2022), potato (Buso et al, 2003), and eggplant (Kaushik, 2019;Kumar et al, 2020); Apiaceae crops, such as carrot, coriander and caraway (Jagosz, 2011;von Maydell et al, 2021;Hanifei et al, 2022); and Leguminosae crops, such as common bean (Goncalves-Vidigal et al, 2008) and pea (Sharma et al, 2023).…”
Section: Heterosis and The Starting Point Of Knowledgementioning
confidence: 99%